Calcium and boron foliar application in the production and quality of sweet pepper seeds - Cardoso, Antonio Ismael Inácio [UNESP]; Colombari, Lidiane F. [UNESP]; Silva, Gustavo F. [UNESP]; Chaves, Prínscilla Pâmela N. [UNESP]; Nogueira, Bianca B. [UNESP]; Putti, Fernando F. [UNESP] (FapUNIFESP (SciELO), 2022)
Calcium and boron are important nutrients in pollen grain formation and seed production. As they are little mobile in plants, it is common to be supplied via foliar application. The objective of this research was to evaluate the production and quality of sweet pepper seeds with calcium and boron application directed to flowers and fruits. The experimental design was in randomized blocks, with seven replications. Four treatments were evaluated: isolated calcium (0.2%) application, isolated boron (0.1%) application, combined application of calcium (0.2%) and boron (0.1%), and the control without calcium and without boron. The characteristics evaluated were number of pollen grains, number of seeds per fruit; 1000 seed weight; physiological quality of seeds (germination, first germination count, and germination speed index) and protein (albumin, globulin, prolamine and glutelin) contents in seeds. Both the application of calcium and boron did not affect the physiological quality of the seeds. Boron application reduced seed production and the 1000 seed weight, while calcium application increased the number of pollen grains, seed production and seed albumin content, and, therefore, the application of calcium in the production of sweet pepper seeds is recommended.
Aplicação foliar de cálcio e boro na produção e qualidade de sementes de pimentão
Keywords: Capsicum annuum; germination; pollen; protein; vigor